The Influence of Bank-Specific, Industry-Specific, and Macroeconomic Factors on Conventional Bank Performance in Indonesia - Veronika Mutianingsih; Mela Aryasari; Fajar Rahmana; Henny Setyo Lestari; Farah Margaretha Leon (Journal of Social Research, 2023)
This research aims to examine the influence of Liquidity, Bank Size, Operational Efficiency, Asset Quality, CAR, NPL, LDR, Asset Share, Average Exchange Rate, and Inflation Rate on the performance of conventional banks. The research sample used was conventional banks listed on the Indonesia Stock Exchange for the period 2019 - 2022. Data was taken from time series data for 2019 - 2022 for the independent variable and bank performance as the dependent variable. The methodology of this research is OLS with Eviews 12 software. The findings in this research are that Liquidity, Bank Size, Operational Efficiency, Asset Quality, CAR, NPL, LDR, Asset Share, Average Exchange Rate, and Inflation Rate simultaneously influence the performance of conventional banks. Bank size, operational efficiency, asset quality, CAR, and NPL, have a significant effect on changes in conventional bank performance as measured by ROA. Bank Size, Operational Efficiency, CAR, NPL have a significant effect on changes in conventional bank performance as measured by ROE. Bank size, operational efficiency, CAR, NPL, LDR, and inflation rate have a significant effect on changes in conventional bank performance as measured by NIM. Bank Size and CAR have a positive and significant effect on changes in conventional bank performance, while Operational Efficiency and NPL have a negative and significant effect on changes in conventional bank performance. Banks can take advantage of large bank size and CAR opportunities to improve their performance so that investors are interested in buying bank shares. Operational efficiency and low and controlled NPL will increase banking profits, especially in conventional banks, thereby improving the bank's performance. It is hoped that the results of this research can provide input for banks and investors to consider bank size, operational efficiency, CAR, and NPL in managing their business and in making investment decisions.